2014
DOI: 10.1021/jf404310y
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Polymethoxylated Flavones from “Guangchenpi”, the Edible and Medicinal Pericarps of Citrus reticulata ‘Chachi’

Abstract: The present study found that the supercritical fluid extract of "Guangchenpi" possessed in vitro antiviral activity against respiratory syncytial virus (RSV). Bioassay-guided isolation and identification of this extract led to obtain five active polymethoxylated flavones (1-5). Cytopathic effect (CPE) reduction assay exhibited that tangeretin (2) and nobiletin (3), two major polymethoxylated flavones in the extract, possessed better anti-RSV effect comparable to the positive control ribavirin. Plaque reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(57 citation statements)
references
References 32 publications
1
56
0
Order By: Relevance
“…As shown in Table 3, (10) showed potent anti-RSV activity comparable to the positive drug ribavirin. In our previous studies, we have found that caffeoyl acid derivatives from natural medicines had potent anti-RSV activities [36,[38][39][40]. Compound 10 is a flavonoid glycoside with a cis-coumaroyl connection.…”
Section: Anti-rsv Activitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Table 3, (10) showed potent anti-RSV activity comparable to the positive drug ribavirin. In our previous studies, we have found that caffeoyl acid derivatives from natural medicines had potent anti-RSV activities [36,[38][39][40]. Compound 10 is a flavonoid glycoside with a cis-coumaroyl connection.…”
Section: Anti-rsv Activitiesmentioning
confidence: 99%
“…CPE reduction assay was adopted to screen the anti-RSV activities of the isolated compounds as described in the previous reports [36,38]. First of all, the cytotoxic activities of the ethanol extract and isolates on host cells were observed under a light microscope (DP70 Olympus, Melville, NY, USA).…”
Section: Anti-rsv Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, Xu et al (2014) showed that polymethoxylaed flavones (PMF) of citrus reticulata extract (tangeretin and nobiletin), are the active components against the respiratory syncytial virus. In addition, the PMF of citrus can be used as nutraceutical supplement or as a therapeutic agent in pre-diabetic and metabolic syndrome conditions (Berim and Gang, 2015).…”
Section: Introductionmentioning
confidence: 99%